1997
DOI: 10.1017/s0022215100137090
|View full text |Cite
|
Sign up to set email alerts
|

An unusual complication of T-tubes

Abstract: The morbidity of long-term ventilation tubes (Goode T-tubes) is often discussed with reference to otorrhoea, tympanosclerosis and long-term perforation. We report three cases of the T-tube slipping into the middle-ear cleft. In two of the three patients this was asymptomatic and the T-tubes were left in situ. In the third patient this complication was documented on three occasions when the T-tube was removed and reinserted for recurrent effusions. We are unaware of this complication being previously reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 7 publications
1
14
0
3
Order By: Relevance
“…Prior case reports noted Goode, Shah, and Shepard tubes, none of which were seen in our study [11,12]. This suggests that the process of medial migration is not tube-dependent.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Prior case reports noted Goode, Shah, and Shepard tubes, none of which were seen in our study [11,12]. This suggests that the process of medial migration is not tube-dependent.…”
Section: Discussionsupporting
confidence: 63%
“…An extensive literature review revealed only two articles dedicated to this complication [11,12]. Both of these articles provide theories on medial migration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations